2018
DOI: 10.1002/2017jd027697
|View full text |Cite
|
Sign up to set email alerts
|

Added Value of Assimilating Himawari‐8 AHI Water Vapor Radiances on Analyses and Forecasts for “7.19” Severe Storm Over North China

Abstract: Himawari‐8 is the first launched and operational new‐generation geostationary meteorological satellite. The Advanced Himawari Imager (AHI) on board Himawari‐8 provides continuous high‐resolution observations of severe weather phenomena in space and time. In this study, the capability to assimilate AHI radiances has been developed within the Weather Research and Forecasting (WRF) model's data assimilation system. As the first attempt to assimilate AHI using WRF data assimilation at convective scales, the added … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 60 publications
(76 reference statements)
1
37
0
Order By: Relevance
“…Although IR radiance assimilation has been operationally and successfully utilized at many centers, Migliorini () proved that sensors with more spectral channels are advantageous to assimilation of transformed retrievals. In a recent study, Wang et al () showed a positive impact from AHI radiance assimilation in predicting heavy precipitation from 19 to 20 July 2016 in Beijing. In another study, Wang, Li, et al () compared AHI radiance assimilation and LPW assimilation; they demonstrated that assimilation of the three derived LPWs yielded improved precipitation prediction.…”
Section: Three Lpw Retrieved From Himawari‐8 Ahi Radiance Measurementsmentioning
confidence: 99%
“…Although IR radiance assimilation has been operationally and successfully utilized at many centers, Migliorini () proved that sensors with more spectral channels are advantageous to assimilation of transformed retrievals. In a recent study, Wang et al () showed a positive impact from AHI radiance assimilation in predicting heavy precipitation from 19 to 20 July 2016 in Beijing. In another study, Wang, Li, et al () compared AHI radiance assimilation and LPW assimilation; they demonstrated that assimilation of the three derived LPWs yielded improved precipitation prediction.…”
Section: Three Lpw Retrieved From Himawari‐8 Ahi Radiance Measurementsmentioning
confidence: 99%
“…According to incomplete statistics (Sun et al, ), including the 20J event, since 2006, approximately 11 extreme severe rain events occurred in Beijing (an extreme severe rain event in Beijing must satisfy the condition that its precipitation is above 100 mm/day at any representative weather station among the 14 districts/counties of Beijing, with a rain intensity of 40 mm/hr appearing at one or more automatic weather stations; Sun et al, ). Compared to the recent 10 extreme severe rain events, three notable features were found in the 20J event (Lei et al, ; Sun et al, ; Wang et al, ; Zhao et al, ): (i) Its duration was long, and its area‐averaged precipitation (over Beijing) was the largest; (ii) its strongest precipitation rate was small (≤60 mm/hr), and the convection was relatively shallow (reflectivity above 15 dBZ was mainly located below 8 km; Lei et al, ); and (iii) having entered the mature stage, the cyclone extended from 950 hPa (near the surface) to up to 200 hPa, that is, the entire troposphere. This is the only special case (in terms of thickness) for the recent 11 extreme severe rain events over Beijing.…”
Section: Introductionmentioning
confidence: 99%
“…It ranges from 0 to infinity with 1 representing the perfect score of BS. The BS measures the ratio of the frequency of forecast events to the frequency of observed events, indicating whether the forecast system has the tendency to overpredict (BS > 1) or underpredict (BS < 1) rainfall events [31]. Figure 9 shows the FSS, ETS, and BS as a function of threshold for 24 h accumulated rainfall.…”
Section: Rainfall Forecast Skill Scoresmentioning
confidence: 99%